Organization and Implementation of a Stroke Center in Panamá, a Model for Implementation of Stroke Centers in Low and Middle Income Countries - Novarro-Escudero, Nelson; Moon, Yoon Ji; Olmedo, Argelis; Ferguson, Teresa; Caballero, Ileana; Onodera, Eduardo; Effio, Euclides; Klein, Lisa M.; Zink, Elizabeth K.; Johnson, Brenda; Urrutia, Victor C. (Frontiers in Neurology, 2021)
Background. Stroke is the second leading cause of death & disability worldwide. Stroke centers have become a central component of modern stroke services in many high-income countries, but their feasibility and efficacy in low, middle, and emerging high-income countries are less clear. Also, despite the availability of international guidelines, many hospitals worldwide do not have organized clinical stroke care. We present a methodology to help hospitals develop stroke centers and review quality data after implementation. Objectives. To describe and compare demographics, performance, and clinical outcomes of the PSHPP stroke center during its first three years 2017-2019. Methods. Hospital Punta Pacífica (PSHPP) was organized to implement protocols of care based on the best practices by international guidelines and a quality improvement process. The methodology for implementation adapts a model for translating evidence into practice for implementation of evidence-based practices in medicine. This is a retrospective study of prospectively collected quality data between March of 2017 to December of 2019 for patients admitted to PSHPP with primary diagnosis stroke. Data collected include demographics, clinical data organized per the Joint Commission’s STK Performance Measures, door to needle, door to groin puncture, 90 day modified Rankin Score, and hemorrhagic complications from IV thrombolysis and mechanical thrombectomy. Primary outcome: year over year proficiency in documenting performance measures Secondary outcome: year over year improvement. Results. A total of 143 patients were admitted for acute ischemic stroke, TIA, or hemorrhagic stroke. Of these, 36 were admitted in 2017, 50 in 2018, and 57 in 2019. Performance measure proficiency increased in the year-over-year analysis as did the total number of patients and the number of patients treated with IV thrombolysis and mechanical thrombectomy. Conclusions. We present the methodology and results of a stroke program implementation in Panama. This program is the first in the country and in Central America to achieve Joint Commission International certification as a Primary Stroke Center. We postulate that the dissemination of management guidelines is not sufficient to encourage the development of stroke centers. The application of a methodology for translation of evidence into practice with mentorship facilitated the success of this program.